The pirates' a-r-r-r-r-guments: new perspectives on social deviance in the context of the information society - Saturnino, Rodrigo (2013)
The information sharing on the Internet created a dilemma on the private property ontology. The attempt to put immaterial things in a monopoly has, apparently, failed considering the so-called digital piracy. Socialize this practice as a deviant, injurious and violator act of the social norms is a massive way used to prevent the “non- authorized” access of information protected by the law. The normative approach about the digital piracy points how our moral values confront the ontological “failure” of the property's idea: not only by the legal trend, but framing new ethical behaviours within old identity patterns. In this paper I use the case of the Pirate Party to verify how the Movement reorients the social function of deviance turning it in a benefit for their political action. To test my idea, I establish some connections between their arguments and the so-called "Sociology of Deviance", focusing in Becker's and Goffman's contributions. My analysis was based on the official documents and some interviews with interlocutors of Sweden, Brazil and Portugal.